Is language laterality related to language abilities? - Bruckert, L (2016)
It is well known that language processing depends on specialized areas in the left side of the brain in the majority of the population. A popular view is that developmental language disorders result from a poorly lateralized brain, but evidence in support of this has been weak and inconsistent. In this thesis, I investigated language-related asymmetries in brain structure and function, and their behavioural relevance in both individuals with specific language impairment (SLI) and typically developing adults. Combining different brain imaging techniques, I looked at group-level as well as individual estimates of language laterality and its relationship to language abilities. The aim of my first two studies was to investigate the neural underpinnings of SLI in terms of white matter microstructure and functional organization associated with auditory processing. For this, diffusion and functional MRI data was obtained in a small number of families with a history of SLI and in control families. Compared with neurotypical controls, children with SLI had lower white matter integrity in the corpus callosum, and in white matter areas corresponding to the dorsal and ventral language pathways. The expected functional lateralization for auditory processing was not observed in either group. In the second half of my thesis, I assessed language laterality in 215 neurotypical adults. I demonstrated that functional transcranial Doppler (FTCD) ultrasonography could reliably assess functional lateralization across different language processes. From this large group, I identified 16 individuals with atypical language lateralization and compared them to a group of 16 typically lateralized individuals using a combination of FTCD, MRI and behavioural measures of language laterality and language abilities. The two groups differed significantly in terms of lateralization assessed by functional MRI and diffusion imaging. The atypical group had lower left and greater right hemisphere activation compared with the typical group, and lacked the leftwards asymmetry in the ventral language tract seen in the typical group. The groups did not differ in terms of cognitive measures. Different functional laterality assessments were concordant in the typically lateralized individuals but were inconsistent in the individuals assessed as atypical by FTCD. In brief, my findings suggest that for some individuals language lateralization may be unstable and varies depending on task or other factors. Even so, such differences do not appear to have consequences for language or other cognitive development.